ISLAMIC BOARDING SCHOOL IN THE MIDDLE OF THE DIGITAL ERA COMMUNICATION CRISIS - Lutfiatun N, Alfina; Aimah, Siti (As-Sulthan Journal of Education, 2024)
This research aims to explore the challenges and opportunities faced by Islamic boarding schools in facing the communication crisis in the digital era, as well as how Islamic boarding schools can adapt digital technology in their education and preaching. The method used is a qualitative approach with case studies in several Islamic boarding schools representing various levels of technology adoption. Data collection techniques were carried out through in-depth interviews with Islamic boarding school administrators, ustaz and Islamic boarding school students, as well as direct observation of activities in Islamic boarding schools and analysis of digital documentation such as social media and preaching videos. The collected data was then analyzed using thematic analysis techniques to identify main themes regarding the use of technology, communication challenges and strategies implemented by Islamic boarding schools. The research results show that Islamic boarding schools face difficulties in adopting technology due to limited resources and digital skills, but also find opportunities to expand the reach of da'wah and education through digital media. This research suggests that Islamic boarding schools improve the digital skills of managers and students, and utilize technology effectively without reducing the traditional values ​​taught. These findings provide recommendations for developing digital communication in Islamic boarding schools so that they remain relevant in the digital era.